Edmund spenser's "The faerie queene" : a reading guide - Zurcher, Andrew (Reading guides to long poems., 2011)
Introduces a Renaissance masterpiece to a modern audience This Guide will help new readers to understand and enjoy The Faerie Queene, drawing attention to its various ironies, its self-reflexive construction, its visual emphasis and the timeless ethical, political, and literary questions that it asks of all of us. The book includes key selections from the poem (each accompanied by a headnote, commentary and glosses), historical and critical discussions, teaching and learning plans and a guide to further resources in electronic and print media. Key Features Contains substantial selections from The Faerie Queene Provides an integrated introduction to Spenser's life, the intellectual and historical context of his writing and the poem's critical reception Includes a range of suggestions for teaching and learning about the poem, both in formal seminars and through independent study Contains a bibliography of further resources, including a list of editions, a list of key critical studies of the poem and a selection of useful websites